Highly ordered TiO2 nanotube arrays and photoelectrocatalytic oxidation of aromatic amine - Cardoso, Juliano Carvalho [UNESP]; Lizier, Thiago Mescoloto [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2010)
Self-organized Ti/TiO2 nanotubular array electrodes may be achieved by simple electrochemical anodization of Ti foil in NH4F/glycerol water solution. The photocurrent on nanotubular layers is remarkably improved in relation to that obtained on comparable nanoporous TiO2 films created by a sol gel process. The anatase form is priori in the highly ordered TiO2 annealed at 450 degrees C which improves its photoactivity. Both electrodes promote complete degradation of the investigated aromatic amine ODAN (4,4'-oxydianiline) after 120 min of photoeletrocatalytic oxidation with potential of 1.5V and UV irradiation. But, the ODAN mineralization is about 50% more efficient on nanotubular electrodes. The best experimental conditions were found to be pH 2.0 and 0.1 mol L-1 Na2SO4 when the photoelectrode was biased at +1.5 V (vs. SCE). Complete mineralization of the aromatic amine content (100% TOC reduction) was achieved after 2 h. Effects of other electrolytes, pH, amine concentration and applied potentials also have been investigated and are discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aromatic amines; Photoelectrocatalysis; TiO2 nanotubes array electrodes; 4,4 '-Oxydianiline; Amine removal